A dynasty of western outlaws - Wellman, Paul I. (Paul Iselin), 1898-1966 (University of Nebraska Press, 1986)
The organized gangs of robbers and killers who roamed the Midwest and Southwest from the 1860s to the 1930s went to the same school and were succored by each other's notoriety. So Paul I. Wellman makes a case for "the contagious nature of crime." William Quantrill and his guerrillas established a criminal tradition that was to link the Iames, Dalton, Doolin, Jennings, and Cook gangs; Belle and Henry Starr; Pretty Boy Floyd; and others in "a long and crooked train of unbroken personal connections."--Publisher description